Plant protein-derived peptides: frontiers in sustainable food system and applications - Nirmal, Nilesh; Khanashyam, Anandu Chandra; Shah, Kartik; Awasti, Nancy; Sajith Babu, Karthik; Ucak, İlknur and Afreen, Maliha and Hassoun, Abdo and Tuanthong, Arthittaya (Frontiers in Sustainable Food Systems, 2024)
Plant proteins have been considered a potential source of bio-functional peptides, which can be beneficial for human health. The potent antioxidant properties of plant-based peptides protect against oxidative damage and associated diseases. Despite a significant number of studies on the preparation and biological functions of plant-based peptides, only a limited number of peptides are commercially utilized. The systematic studies of the extraction, optimization, isolation, pharmacokinetics, stability, and safety aspects of plant protein-derived peptides (PPDP) are in progress. Also, the molecular mechanism of action and health benefits of bioactive PPDP is still lacking. Hence, this review provides a comprehensive discussion of various plant protein sources to end-product applications of PPDP. In this context, different plant sources explored for functional and bioactive PPDP have been presented. The green biotechnological techniques such as fermentation and enzymatic hydrolysis for extraction of PPDP have been described. The functional and biological properties of PPDP have been revisited. The most important part of the application which includes the stability and bioavailability of PPDP has been discussed. Additionally, the health impact of PPDP administration has been summarized. Lastly, future perspectives and concluding remarks have been documented.